Mongush Karma Dombuevich - Munzuk, Svetlana M. (The New Research of Tuva, 2014)
Encyclopedic article. Mongush Karma Dombrowicz (25.05.1936–24.06.2012) — the first professional cameraman Tuva, Honored worker of culture of the Tuva ASSR, holder of the order "For valorous work".